2017
DOI: 10.4269/ajtmh.16-0558
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adherence on the Impact of a School-Based Water, Sanitation, and Hygiene Intervention in Mali

Abstract: Abstract. Studies assessing the impacts of school-based water, sanitation, and hygiene (WASH) interventions have revealed inconsistent improvements in pupils' health and educational outcomes. This may be in part due to suboptimal project fidelity or adherence. As part of a matched-control trial of a comprehensive school-based WASH project in Mali, we measured the degree to which schools met four prespecified WASH targets, comprised of 15 criteria, 0-3 years after program implementation. We compared achievement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…The delivery of improved water at schools can contribute to the improved health and educational performance. Further, water helps to maintain environmental and personal hygiene, decrease chances of dehydration at schools, and ultimately contribute to improved cognitive abilities [27,46]. The geographical differences in pathogen-related health risks between North and South Sindh were likely due to different types of water sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delivery of improved water at schools can contribute to the improved health and educational performance. Further, water helps to maintain environmental and personal hygiene, decrease chances of dehydration at schools, and ultimately contribute to improved cognitive abilities [27,46]. The geographical differences in pathogen-related health risks between North and South Sindh were likely due to different types of water sources.…”
Section: Discussionmentioning
confidence: 99%
“…The headmaster of each school was interviewed, and drinking-water samples and structured observations of WASH were collected. ODK Collect Android Software was used to collect survey data [27]. Structured observations of water facilities were carried out, to assess the availability, accessibility, and functionality of water facilities.…”
Section: Samplingmentioning
confidence: 99%
“…While school-based WASH interventions in low-income and middle-income countries have been examined with regards to a wide range of health and educational outcomes, including: diarrhoea, respiratory infection, school attendance and health outcomes in the domestic environment,9–13 these studies have shown that the impact on such outcomes is inconsistent. For the most part, this variability has been viewed through the lens of intervention fidelity and compliance— the extent to which schools and/or implementing organisations have provided WASH services in schools routinely and in a manner consistent with intervention protocols 14 15. However, for school-based hygiene interventions to result in health or educational impacts, they must also successfully change students’ hygiene behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Matched comparison schools were located within the same educational district and matched to beneficiary schools based on baseline enrollment size and school WASH characteristics. Detailed methods of the parent study and the as-treated analysis are described elsewhere [ 14 , 17 ]. In each school, 20 pupils were randomly selected from a list of all pupils enrolled in classes 1–6 using stratified random sampling based on pupil sex and grade.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the biological plausibility supporting the role of improvements in school WASH conditions on pupil health, results from school WASH evaluations have been mixed [ 6 12 ]. There is some evidence of associations between WASH in schools programs and reductions in diarrhea, acute respiratory infection, soil-transmitted helminth re-infection, and school absence, but results are inconsistent and effects are sometimes evident only among sub-populations [ 6 , 8 , 9 , 13 17 ].…”
Section: Introductionmentioning
confidence: 99%